Techno-Economic Analysis of IoT Networks in 5G - Christos Bouras; Charalampos Chatzigeorgiou; Anastasia Kollia; Philippos Pouyioutas (This article evaluates the Techno-economic analysis of IoT networks in 5G. The study analyzed the proposed model for the Internet of Things and the Femtocell in ascertaining the feasibility of the models for the 5G network. The study entirely majors on th, 2023)
This article evaluates the Techno-economic analysis of IoT networks in 5G. The study analyzed the proposed model for the Internet of Things and the Femtocell in ascertaining the feasibility of the models for the 5G network. The study entirely majors on the analysis of the LoRa WAN network because of its adequate characteristics of low power consumption, easy scalability, and high coverage. It is license-free, which facilitates reduced costs and fast developments. Compared with the expected revenue to be collected during the growth period, the cost elements were Operating Expenditure (OPEX) and Capital Expenditure (CAPEX). The analysis of the results shows that the 5G network is more significant than the 4G LTE because of the lower cost associated with it and the increase in the data transferability that the 5G offers, and the increased number of users.